Slurry
The use of a slurry containing an inorganic solid electrolyte, polyalkylene carbonate, and a stabilizer in solid-state batteries addresses the stability issues by suppressing the degradation of polyalkylene carbonate, resulting in enhanced mechanical stability and prolonged battery lifespan.
Patent Information
- Application Number
- JP2023145757
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-08
- Publication Date
- 2025-03-21
AI Technical Summary
Solid-state batteries require high stability over time due to their long-term storage and usage, and existing methods do not effectively address the degradation of polyalkylene carbonate binders, which affects the mechanical and electrical properties of the batteries.
A slurry comprising an inorganic solid electrolyte, polyalkylene carbonate, and a stabilizer, such as a dithiophosphine ylide generator, is used to form electrolyte layers, positive electrodes, or negative electrodes in solid-state batteries, thereby suppressing the degradation of polyalkylene carbonate and enhancing stability.
The proposed solution effectively suppresses the deterioration of polyalkylene carbonate, leading to improved mechanical stability and prolonged lifespan of solid-state battery components, while maintaining good ionic conductivity.
Smart Images

Figure 2025039023000009 
Figure 2025039023000001 
Figure 2025039023000002
Abstract
Description
[Technical field]
[0001] The present disclosure relates to slurries, particularly slurries used in the fabrication of solid state battery components. [Background technology]
[0002] In recent years, in order to improve the charge / discharge characteristics of in-vehicle secondary batteries and to avoid the dangers associated with the flammable solvents contained in current liquid electrolytes, development of solid-state batteries (also called all-solid-state batteries) in which the components of the battery are made of solid materials has been progressing.
[0003] Patent Document 1 discloses the use of an additive for all-solid-state secondary batteries containing polyalkylene carbonate as a method for improving battery characteristics such as charge / discharge capacity. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2017 / 030127 Summary of the Invention [Problem to be solved by the invention]
[0005] Since solid-state batteries and solid-state battery components (electrolyte layer, positive electrode, or negative electrode) are likely to be stored or used for a long period of time, high stability over time is required. An object of the present disclosure is to provide a novel method for improving the stability over time of solid-state batteries. [Means for solving the problem]
[0006] The present disclosure includes the following aspects: [Section 1] A slurry for forming an electrolyte layer, a positive electrode, or a negative electrode in a solid-state battery, The slurry comprises an inorganic solid electrolyte, a polyalkylene carbonate, and a stabilizer for the polyalkylene carbonate. [Section 2] Item 2. The slurry according to item 1, wherein the stabilizer is at least one selected from the group consisting of a hydroxyl group protecting agent, and a carboxylic acid or a salt thereof. [Section 3] Item 3. The slurry according to item 2, wherein the stabilizer is a dithiophosphine ylide generator. [Section 4] 4. The slurry according to any one of items 1 to 3, wherein the inorganic solid electrolyte is a sulfide solid electrolyte. [Section 5] the slurry comprises a stabilizer for the polyalkylene carbonate and / or a reaction product of the polyalkylene carbonate and the stabilizer; the stabilizer is a dithiophosphine ylide generator, 5. The slurry according to any one of items 1 to 4, wherein the inorganic solid electrolyte is a sulfide solid electrolyte. [Section 6] The polyalkylene carbonate has the following formula (I): -(-(C=O)-OR P1 -O-(-R P2 -O-) m -) n - (I) [In the formula, R P1 and R P2 each independently represents a chain alkylene group having 1 to 10 carbon atoms or a cycloalkylene group having 3 to 10 carbon atoms, m is 0, 1 or 2, and n is 10 to 15,000. 6. The slurry according to any one of items 1 to 5, wherein the slurry is represented by the following formula: [Section 7] 7. The slurry according to any one of items 1 to 6, which is for forming an electrolyte layer. [Section 8] 7. The slurry according to any one of items 1 to 6, which is for forming a positive electrode. [Section 9] 7. The slurry according to any one of items 1 to 6, which is for forming a negative electrode. [Section 10] 10. An electrolyte layer, a positive electrode, or a negative electrode obtained by applying and drying the slurry according to any one of items 1 to 9. [Section 11] Item 11. A solid-state battery comprising the electrolyte layer, the positive electrode, or the negative electrode according to item 10, wherein the polyalkylene carbonate is decomposed and removed. [Section 12] The method includes a step of applying and drying the slurry according to any one of items 1 to 9 to obtain an electrolyte layer, a positive electrode, or a negative electrode; How solid-state batteries are manufactured. Effect of the Invention
[0007] By using the slurry according to the present disclosure in the production of a battery, deterioration of the polyalkylene carbonate functioning as a binder can be suppressed, and good stability over time, in particular mechanical stability over time, can be imparted to the solid-state battery or solid-state battery components (electrolyte layer, positive electrode, or negative electrode). [Brief description of the drawings]
[0008] [Figure 1] 1 shows the results of TG / DTA in Examples and Comparative Examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] <Slurry> The slurry of the present disclosure is used to form a solid battery component (electrolyte layer, positive electrode, or negative electrode) by applying the slurry to a substrate and then drying to form the battery component.
[0010] The slurry in the present disclosure includes an inorganic solid electrolyte and a polyalkylene carbonate. It may further include other components, and in the case of a slurry for forming a positive electrode, it includes a positive electrode active material, and in the case of a slurry for forming a negative electrode, it includes a negative electrode active material. In the slurry, each component is dissolved or dispersed in a dispersion medium.
[0011] [Inorganic solid electrolyte] The slurry contains an inorganic solid electrolyte. As the inorganic solid electrolyte in the present disclosure, a known inorganic solid electrolyte can be used. The inorganic solid electrolyte may be, for example, a sulfide, an oxide, an oxynitride, a nitride, a hydride, a halide, or a combination thereof. The inorganic solid electrolyte may be a crystalline or amorphous type, and is preferably an amorphous type.
[0012] Sulfide electrolyte is Z2S-M x S y (Z is Li and Na, M is one or more selected from P, Si, Sn, Sb, Ge, B, Al, and Ga, x and y are numbers that give a stoichiometric ratio according to the type of M, M x S y Examples of sulfide electrolytes are P2S5, SiS2, SnS2, Sb2S3, GeS2, B2S3, Al2S3, and Ga2S3. n S m -ZX (Z is Li and Na, M is P, Si, Sn, Sb, Ge, B, Al and Ga, X is one or more selected from Cl, Br and I, n and m are numbers that give a stoichiometric ratio according to the type of M, M n S m The sulfide electrolyte may be a sulfide electrolyte represented by P2S5, SiS2, SnS2, Sb2S3, GeS2, B2S3, Al2S3, Ga2S3, etc. The sulfide electrolyte may have a phosphorus oxide structure (e.g., PO4, P2O5). Specific examples of the sulfide electrolyte include Li2S-P2S5, Li2S-SiS2, Na2S-P2S5, Na2S-SiS 2、 Li2S-P2S5-GeS2, Li2S-P2S5-B2S3, Li2S-P2S5-LiCl, Li2S-P2S5-LiI, Li2S-P2S5-LiBr-LiCl, Li2S-SiS2-LiBr, Na2S-P2S5-LiBr, Na2S-SiS2-LiI, Li2 S-B2S3-LiI, Li2S-Si2S-Li3PO4, Li2S-SiS2-Li3PO4, Li2S-SiS-LiPO4, Li2S-LiI-P2O5, LiI-P2S5-Li3PO4, LiI-LiBr-Li3PS4, Li2S-P2S5-LiI-LiBr, Li 10 GeP2S 12The sulfide electrolyte may be Li2S-P2S5 (the molar ratio (Li2S / P2S5) may be 0.1 or more, 1 or more, 2 or more, or 5 or more, and 30 or less, 20 or less, or 10 or less, for example, 2 to 5 (for example, 3 (i.e., Li3PS4)).
[0013] The oxide electrolyte is Z2O-M x O y (Z is Li and Na, M is one or more selected from P, Si, Ge, B, Al and Ga, x and y are numbers that give a stoichiometric ratio according to the type of M, M x O y Examples of oxide electrolytes are P2O5, SiSO2, GeO2, B2O3, Al2O3, and Ga2O3. n O m -ZX (Z is Li and Na, M is P, Si, Ge, B, Al and Ga, X is one or more selected from Cl, Br and I, n and m are numbers that give a stoichiometric ratio according to the type of M, M n O m The oxide electrolyte may be an oxide electrolyte represented by P2O5, SiO2, GeO2, B2O3, Al2O3, Ga2O3, etc. The oxide electrolyte may contain Li2O, for example, Li2O-P2O5 (the molar ratio (Li2S / P2O5) is 0.1 or more, 1 or more, 2 or more, or 5 or more, and 30 or less, 20 or less, or 10 or less). The oxide electrolyte may have a phosphorus oxide structure (e.g., PO4, P2O5). The oxide electrolyte may have an inverse perovskite structure (e.g., Li3OX (X=Cl, Br)). Specific examples of the oxide electrolyte include Li2O-P2O5, Li2O-SiO2, Na2O-P2O5, Na2O-SiO 2、 Li2O-P2O5-GeO2, Li2O-P2O5-B2O 3、Li2O-P2O5-LiCl, Li2O-P2O5-LiI, Li2O-P2O5-LiBr-LiCl, Li2O-SiO2-LiBr, Na2O-P2O5-LiBr, Na2O-SiO2-LiI, Li2O-B2O3-LiI, Li2O-Si2O-Li3PO4, Li2O-SiO2-Li3PO4, Li2O-SiO-LiPO4, Li2O-LiI-P2O5, LiI-P2O5-Li3PO4, LiI-LiBr-Li3PO4, Li2O-P2O5-LiI-LiBr, Li 3x La 2 / 3-x TiO3 (for example, 0 < x < 0.17), Li 1+x Al x Ti 2-x (PO4)3 (for example, 0 < x < 2), Li7La3Zr2O 12 、Li 1+x Al x Ge 2-x (PO4)3 (for example, 0 < x < 2), Na 1+x Al x Ti 2-x (PO4)3 (for example, 0 < x < 2), Na7La3Zr2O 12 、及びNa 1+x Al x Ge 2-x (PO4)3 (for example, 0 < x < 2), lithium silicate (Li 3.5 Si 0.5 P 0.5 O4), lithium titanium phosphate (LiTi2(PO4)3), lithium titanate (Li4Ti5O 12 ), lithium germanium phosphate (LiGe2(PO4)3), lithium cobalt composite oxides such as LiCoO2 and lithium manganese composite oxides such as LiMnO4, lithium nickel composite oxides, lithium vanadium composite oxides, lithium zirconium composite oxides, lithium hafnium composite oxides, inverse perovskite structure electrolytes (for example, Li-2OHBr, Li3OBr, Li3OCl, Li3OBr 0.5 Cl 0.5 ) etc. can be mentioned.
[0014] Examples of other inorganic solid electrolytes include crystalline nitrides such as Li3N, Li3PO (4-3 / 2w) N w(w<1), xLi(CB9H 10 )-(1-x)Li(CB 11 H 12 ) and halides such as Li3YCl6. In addition to the inorganic solid electrolyte, other known solid electrolytes may be included.
[0015] In the solid-state battery, examples of the inorganic solid electrolyte in the positive electrode-forming slurry or the negative electrode-forming slurry may be the same as the inorganic solid electrolyte in the electrolyte layer-forming slurry described above, and the inorganic solid electrolyte in the positive electrode-forming slurry and the negative electrode-forming slurry may be the same as the inorganic solid electrolyte in the electrolyte layer-forming slurry.
[0016] The inorganic solid electrolyte may be in a powder form before being made into a slurry, and the average particle diameter (D 50 ) may be 0.1 μm or more, 0.5 μm or more, or 1 μm or more, and the inorganic solid electrolyte powder may have a volume average particle size of, for example, 50 μm or less, 25 μm or less, or 5 μm or less. The average particle size may be a particle size corresponding to a cumulative 50% in a volume-based particle size distribution measured using a laser diffraction / light scattering type particle size distribution meter. Alternatively, a value measured using an electron microscope (e.g., scanning electron microscope: SEM) or the like may be used.
[0017] (Amount of inorganic solid electrolyte) The amount of the inorganic solid electrolyte in the slurry solid content for forming the electrolyte layer may be 75% by mass or more, 80% by mass or more, 85% by mass or more, 90% by mass or more, or 95% by mass or more, preferably 90% by mass or more. The amount of the inorganic solid electrolyte in the slurry solid content for forming the electrolyte layer may be 99% by mass or less, 95% by mass or less, 90% by mass or less, 85% by mass or less, or 80% by mass or less. The above range is suitable from the viewpoint of improving the battery characteristics, and the effects of the present disclosure can be more suitably exhibited.
[0018] The amount of inorganic solid electrolyte in the slurry solid content for forming a positive electrode may be 1% by mass or more, 5% by mass or more, 10% by mass or more, 15% by mass or more, 20% by mass or more, or 30% by mass or more, preferably 5% by mass or more. The amount of inorganic solid electrolyte in the slurry solid content for forming a positive electrode may be 60% by mass or less, 50% by mass or less, 40% by mass or less, 30% by mass or less, 20% by mass or less, or 10% by mass or less, preferably 30% by mass or less. By being in the above range, it is possible to realize an improvement in energy density and an improvement in charge / discharge capacity due to the formation of a sufficient ion conduction path.
[0019] The amount of inorganic solid electrolyte in the slurry solid content for forming the negative electrode may be 1% by mass or more, 5% by mass or more, 10% by mass or more, 15% by mass or more, 20% by mass or more, or 30% by mass or more, preferably 10% by mass or more. The amount of inorganic solid electrolyte in the slurry solid content for forming the negative electrode may be 60% by mass or less, 50% by mass or less, 40% by mass or less, 30% by mass or less, 20% by mass or less, or 10% by mass or less, preferably 50% by mass or less. By being in the above range, it is possible to realize an improvement in energy density and an improvement in charge / discharge capacity due to the formation of a sufficient ion conduction path.
[0020] [Polyalkylene carbonate] The slurry in the present disclosure contains polyalkylene carbonate. The polyalkylene carbonate functions as a binder. The binder has the ability to bind solid particles (e.g., inorganic solid electrolyte and active material, active material particles, inorganic solid electrolytes, electrolyte layer and positive electrode or negative electrode) after the slurry is applied. The polyalkylene carbonate has good binding properties, and can also have a low thermal decomposition onset temperature and good ionic conductivity after thermal decomposition.
[0021] The residual rate of the polyalkylene carbonate in the slurry after standing for 5 days may be 25% or more, 30% or more, 35% or more, 40% or more, 45% or more, 50% or more, 55% or more, 60% or more, 65% or more, 70% or more, 75% or more, 80% or more, 85% or more, 90% or more, 95% or more, or 99% or more, and the higher the rate, the better. Here, the condition for standing is a temperature of 25°C. Standing is performed under dry conditions, and for example, the humidity during standing is a dew point temperature of -85°C. The method for measuring the residual rate after standing for 5 days can be performed by using a spectroscopic method such as IR measurement, as described in the examples.
[0022] Polyalkylene carbonates are alkylene groups (-R P A compound having a repeating unit containing a carboxylate group (-O-(C=O)-O-), and represented by the following formula: -(-(C=O)-OR P -O-)- [In the formula, R P is an alkylene group. or may consist of repeat units represented by said formula.
[0023] R P The number of carbon atoms in R may be 1 or more, 2 or more, 3 or more, 4 or more, or 5 or more, for example, 2 or more. P The number of carbon atoms in R may be 20 or less, 15 or less, 10 or less, 8 or less, or 6 or less, for example, 10 or less. P R may be linear, branched, or cyclic. P may be an ethylene group, a propylene group, or a cyclohexylene group. The above range is preferable from the viewpoints of availability and improving the effect of reducing the interface resistance.
[0024] The mass average molecular weight of the polyalkylene carbonate may be 5000 or more, 10000 or more, 30000 or more, 50000 or more, 100000 or more, or 200000 or more, preferably 30000 or more. The mass average molecular weight of the polyalkylene carbonate may be 2000000 or less, 1500000 or less, 1000000 or less, 750000 or less, 500000 or less, 250000 or less, or 100000 or less, preferably 1000000 or less. By having the mass average molecular weight of the polyalkylene carbonate in the above range, the viscosity when the slurry is prepared, the dispersibility of the electrolyte, active material, conductive assistant, etc., and the coatability of the slurry are appropriate. The molecular weight can be determined by GPC, for example, using a Waters 2695 separation module manufactured by Nihon Waters equipped with a column (manufactured by Showa Denko K.K., product name: Shodex OHPac SB-800 series), with the column temperature at 40°C, a 0.03 mol / L lithium bromide-N,N-dimethylformamide solution as the eluent, and a flow rate of 0.65 mL / min, and then comparing the molecular weight measured under the same conditions with that of a known polystyrene.
[0025] The Mw / Mn of the polyalkylene carbonate may be 1 or more, 1.1 or more, 1.2 or more, or 1.3 or more, and may be 20 or less, 15 or less, 10 or less, 5 or less, or 2.5 or less.
[0026] The polyalkylene carbonate has the following formula (I): -(-(C=O)-OR P1 -O-(-R P2 -O-) m -) n - (I) [In the formula, R P1 and R P2 each independently represents a chain alkylene group having 1 to 10 carbon atoms or a cycloalkylene group having 3 to 10 carbon atoms, m is 0, 1 or 2, and n is 10 to 15,000. The polyalkylene carbonate may be represented by the formula:
[0027] In the polyalkylene carbonate represented by formula (I), -(-R P2 -O-) m The ratio of the ether structure represented by - may be 0.1% by mass or more and may be 20% by mass or less.
[0028] The composition ratio of the polyalkylene carbonate can be determined, for example, by using nuclear magnetic resonance spectroscopy. For example, the polyalkylene carbonate is dissolved in deuterated chloroform and heated at 25° C. 1 The composition ratio can be determined by measuring H-NMR and estimating the ratio of the integral value of the peak assigned to hydrogen bonded to the carbon atom adjacent to the carbonate group, which appears in the range of 4.0 to 5.2 ppm, to the integral value of the peak assigned to hydrogen bonded to the carbon atom adjacent to the ether group, which appears in the range of 3.0 to 3.7 ppm.
[0029] R P1 and R P2 Examples of the chain alkylene group having 1 to 10 carbon atoms (preferably 2 to 8 or 2 to 5 carbon atoms) in R include linear alkylene groups such as ethylene group, trimethylene group, tetramethylene group, pentamethylene group, hexamethylene group, heptamethylene group, octamethylene group, nonamethylene group, and decamethylene group, and branched alkylene groups such as propylene group, 1,2-butylene group, and 1,2-dimethylethylene group. P1 and R P2 Examples of the cycloalkylene group having 3 to 10 carbon atoms (preferably 4 to 8 or 4 to 6) in R include cycloalkylene groups such as cyclopropylene group, cyclobutylene group, cyclopentylene group, cyclohexylene group, cyclooctylene group, cyclononylene group, and cyclodecylene group. P1 and / or R P2 R may contain both linear alkylene groups and cycloalkylene groups. P1 and / or R P2may be an ethylene group, a propylene group, or a cyclohexylene group from the viewpoints of availability, a lowering of the thermal decomposition temperature, etc. Suitable examples of the polyalkylene carbonate include polyethylene carbonate, polypropylene carbonate, polycyclohexylene carbonate, etc.
[0030] n may be 10 or more, 50 or more, 100 or more, or 300 or more, and is preferably 100 or more. n may be 15000 or less, 10000 or less, 7500 or less, or 3000 or less, and is preferably 7500 or less. When n is within the above range, the viscosity when the slurry is prepared, the dispersibility of the electrolyte, active material, conductive assistant, etc., and the coatability of the slurry are appropriate.
[0031] The method for producing polyalkylene carbonate is not particularly limited, and a known method for producing polyalkylene carbonate can be used. For example, polyalkylene carbonate can be produced by polymerizing various alkylene oxides with carbon dioxide in the presence of a metal catalyst. Examples of alkylene oxides include ethylene oxide, propylene oxide, 1-butene oxide, 2-butene oxide, isobutylene oxide, 1-pentene oxide, 2-pentene oxide, 1-hexene oxide, 1-octene oxide, 1-decene oxide, cyclopentene oxide, and cyclohexene oxide. These may be used alone or in combination of two or more. Examples of metal catalysts include aluminum catalysts, zinc catalysts, and cobalt catalysts, and these catalysts may be organometallic catalysts. For example, an organozinc catalyst can be used as a catalyst for producing a polyalkylene carbonate having an ether structure as shown in formula (I) (see, for example, JP 2012-224675 A). For the production of polyalkylene carbonates not having an ether structure, an organic cobalt catalyst can be used as the catalyst (see, for example, JP-A-2010-270278).
[0032] (Amount of polyalkylene carbonate) The amount of polyalkylene carbonate may be 0.05% by mass or more, 0.1% by mass or more, 0.3% by mass or more, 0.5% by mass or more, 1% by mass or more, 2.5% by mass or more, 5% by mass or more, preferably 0.1% by mass or more, for example 0.5% by mass or more, in the slurry solid content. The amount of polyalkylene carbonate may be 40% by mass or less, 35% by mass or less, 30% by mass or less, 25% by mass or less, 20% by mass or less, 15% by mass or less, 10% by mass or less, 5% by mass or less, or 3% by mass or less, preferably 30% by mass or less, for example 20% by mass or less, in the slurry solid content. The above range is suitable from the viewpoints of the effect of reducing the interface resistance, the amount of voids generated in the electrolyte layer after the thermal decomposition process described later, and the like, and from the viewpoints of the dispersibility of the slurry, distribution unevenness in the coating film, smoothness and strength of the film, adhesion to the current collector, and uniformity of the film thickness, and the effects of the present disclosure can be more suitably exhibited.
[0033] [Stabilizer] The slurry in the present disclosure may contain a stabilizer for polyalkylene carbonate. It is considered that the decomposition of the polyalkylene carbonate in the slurry is promoted even in the range of room temperature to 80° C. by the inorganic solid electrolyte, active material, etc. functioning as an acid catalyst or a base catalyst. Therefore, it may be important to suppress the decomposition of the polyalkylene carbonate from the preparation of the slurry to before the heat treatment of the battery in order to maintain the mechanical properties or electrical properties of the battery. Here, the stabilizer is capable of stabilizing the polyalkylene carbonate and suppressing the decomposition of the polyalkylene carbonate. Since it is expected that the polyalkylene carbonate will be removed by thermal decomposition after the slurry is applied, it is preferable that the stabilizer has an appropriate stabilizing property.
[0034] The stabilizer for polyalkylene carbonate in the present disclosure may be a hydroxyl group protecting agent, a carboxylic acid or a salt thereof. Although not wishing to be bound by a particular theory, the decomposition mechanism of polyalkylene carbonate is considered to be a depolymerization reaction (unzipping reaction) caused by the terminal hydroxyl group of polyalkylene carbonate nucleophilically attacking the carbonate group in the molecule, or a random decomposition reaction (random chain scission) accompanied by decarboxylation. It is considered that the hydroxyl group protecting agent protects the terminal hydroxyl group of polyalkylene carbonate to suitably suppress the depolymerization reaction, and the carboxylic acid or a salt thereof protects the carbonate group by interacting with the carbonate group by hydrogen bonding or electrostatically, thereby suitably suppressing the random decomposition reaction. For the decomposition of polyalkylene carbonates, see, for example, Phillips et al. (2016). Polymer Degradation and Stability, 125, 129-139. and Varghese et al. (2010). Polymer Degradation and Stability, 95(6), 1039-1044.
[0035] (Hydroxy group protecting agent) The hydroxyl group protecting agent may be a known hydroxyl group protecting agent, for example, an acyl type protecting agent forming an acetyl group, a benzoyl group, etc., a silyl type protecting agent forming a t-butyldimethylsilyl group, a t-butyldiphenylsilyl group, etc., an alkyl type protecting agent forming a methoxymethyl group, a benzyl group, etc., a dithiophosphine ylide generator, etc.
[0036] (Carboxylic acid or its salt) The carboxylic acid or its salt may be a known aliphatic, alicyclic, or aromatic monocarboxylic acid or polycarboxylic acid or its salt. Examples of the carboxylic acid or its salt include saturated mono-fatty acids such as acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, enanthic acid, caprylic acid, pelargonic acid, capric acid, 2-ethyl-hexanecarboxylic acid, undecylic acid, lauric acid, tridecylic acid, myristic acid, pentadecylic acid, palmitic acid, heptadecylic acid, stearic acid, nonadecanoic acid, arachic acid, behenic acid, lignoceric acid, cerotic acid, heptacosanoic acid, montanic acid, melissic acid, and lacteric acid; undecylenic acid. unsaturated mono-fatty acids such as oleic acid, sorbic acid, linoleic acid, linolenic acid, and arachidonic acid; aromatic polycarboxylic acids such as trimellitic acid, trimesic acid, and pyromellitic acid; aliphatic polycarboxylic acids such as succinic acid, adipic acid, azelaic acid, sebacic acid, oxalic acid, fumaric acid, maleic acid, and tetrahydrophthalic acid, and oxypolycarboxylic acids such as tartaric acid, tartronic acid, malic acid, and citric acid; or salts thereof (e.g., alkali metal salts, alkaline earth metal salts).
[0037] (Dithiophosphine ylide generator) As the hydroxyl group protecting agent, a dithiophosphine ylide generating compound is preferable. The dithiophosphine ylide generating agent is represented by the following formula: It is a compound having a 1,3,2,4-dithiadiphosphetane-2,4-disulfide structure represented by TIFF2025039023000001.tif2945, and has the following formula: It can be in equilibrium with a dithiophosphine ylide represented by TIFF2025039023000002.tif24104. Although not wishing to be bound by a particular theory, it is believed that the dithiophosphine ylide generator reacts with the hydroxyl group of the polyalkylene carbonate to function as a hydroxyl group protecting agent. It is also believed that the random decomposition reaction accompanied by decarboxylation can be suppressed by thiocarbonylating the carbonyl group.
[0038] The dithiophosphine ylide generator may be Lawesson's reagent or an analogue of Lawesson's reagent. Examples of dithiophosphine ylide generators include: TIFF2025039023000003.tif2548 [wherein R is an alkyl group (e.g., an alkyl group having 1 to 8 carbon atoms (e.g., methyl, ethyl, isopropyl, butyl)), a benzyl group, a phenyl group, an alkyl group-substituted phenyl group (e.g., a substituted phenyl group substituted with 1 to 3 alkyl groups having 1 to 4 carbon atoms, e.g., a p-methylphenyl group) (also called Davis' reagent or Japanese reagent).] TIFF2025039023000004.tif20109, and Examples include TIFF2025039023000005.tif17112.
[0039] (amount of stabilizer) The amount of the stabilizer may be 0.05% by mass or more, 0.1% by mass or more, 0.3% by mass or more, 0.5% by mass or more, 1% by mass or more, 2.5% by mass or more, 5% by mass or more, preferably 0.1% by mass or more, more preferably 0.5% by mass or more, based on the polyalkylene carbonate. The amount of the stabilizer may be 25% by mass or less, 20% by mass or less, 15% by mass or less, 10% by mass or less, 5% by mass or less, or 3% by mass or less, preferably 20% by mass or less, more preferably 10% by mass or less, based on the polyalkylene carbonate. From the viewpoint of achieving the effects of the present invention well, it is preferable that the stabilizer (for example, a stabilizer that is a hydroxyl group protecting agent) is added in an amount greater than the stoichiometric amount of the polyalkylene carbonate terminal. The amount of the stabilizer may be 5 mol% or more, 10 mol% or more, 30 mol% or more, 75 mol% or more, 100 mol% or more, 150 mol% or more, 200 mol% or more, 300 mol% or more, or 400 mol% or more, preferably 100 mol% or more, based on the polyalkylene carbonate terminal. The amount of the stabilizer may be 1000 mol% or less, 750 mol% or less, 500 mol% or less, 250 mol% or less, or 150 mol% or less, based on the stoichiometric amount of the polyalkylene carbonate terminal. By being within the above range, particularly the above lower limit value or more, the decomposition of the polyalkylene carbonate can be suitably suppressed, and the effects of the present disclosure can be more suitably exhibited. The stabilizer may coexist with a reaction product of the polyalkylene carbonate and the stabilizer, and what was a stabilizer at the time of preparation of the slurry may change over time into a reaction product by reacting a part or all of the stabilizer with the polyalkylene carbonate. The amount of the stabilizer in the above may mean the amount of the stabilizer at the time of preparation of the slurry.
[0040] [(Poly)oxyalkylene] The slurry may contain a (poly)oxyalkylene. The alkylene group of the (poly)oxyalkylene is a linear or branched hydrocarbon group having 2 to 8 carbon atoms, preferably a linear or branched hydrocarbon group having 2 to 4 carbon atoms. The molecular weight of the (poly)oxyalkylene is not particularly limited, but may be a mass average molecular weight of 200 or more, 500 or more, or 1000 or more, and may be 30000 or less, 10000 or less, or 5000 or less. Examples of the (poly)oxyalkylene include glycols (poly(alkylene) glycols) such as (poly)ethylene glycol, (poly)propylene glycol, and (poly)butylene glycol, or alkyl etherified products thereof.
[0041] (Amount of (poly)oxyalkylene) The amount of the (poly)oxyalkylene may be 0.1% by mass or more, 0.5% by mass or more, 1% by mass or more, or 5% by mass or more, based on the polyalkylene carbonate. The amount of the (poly)oxyalkylene may be 10% by mass or less, 6% by mass or less, or 2% by mass or less, based on the polyalkylene carbonate.
[0042] [Alkaline metal inorganic salts] A small amount of an alkali metal inorganic salt may be added to the slurry separately from the inorganic solid electrolyte. The method of addition is not limited, and the alkali metal inorganic salt may be mixed and added to the polyalkylene carbonate in advance, or may be added when the polyalkylene carbonate and the inorganic solid electrolyte are slurried and mixed. Examples of the alkali metal salt include hydroxides, fluorides, chlorides, bromides, iodides, acetates, nitrates, sulfates, phosphates, trifluoromethanesulfonates, perchlorates, bis(fluorosulfonyl)imide salts, tetrafluoroborates, and hexafluorophosphates, and preferred examples are hydroxides or halides. Examples of the metal in the alkali metal salt may be lithium, sodium, potassium, or cesium, and a preferred example is lithium. These may be used alone or in combination of two or more.
[0043] (Amount of alkali metal inorganic salt) The amount of alkali metal inorganic salt added may be 10 ppm or more, 50 ppm or more, 300 ppm or more, or 500 ppm or more, preferably 250 ppm or more, based on the polyalkylene carbonate. The amount of alkali metal inorganic salt added may be 10000 ppm or less, 3000 ppm or less, 2000 ppm or less, or 1000 ppm or less, preferably 2500 ppm or less, based on the polyalkylene carbonate. By adding a small amount of alkali metal to the slurry, the thermal decomposition starting temperature of the polyalkylene carbonate can be lowered.
[0044] [Dispersion medium] The slurry in the present disclosure contains a dispersion medium, which gives the slurry fluidity and enables the slurry to be applied to a substrate.
[0045] The dispersion medium used is one that dissolves or disperses polyalkylene carbonate without affecting the properties of other components, and is usually an organic solvent. Specifically, saturated chain hydrocarbons such as n-pentane, n-hexane, heptane, n-octane, nonane, decane, undecane, dodecane, tridecane, tetradecane, etc., halogen-substituted saturated chain hydrocarbons such as carbon tetrachloride, chloroform, dichloroethane, etc., saturated cyclic hydrocarbons such as cyclohexane, cycloheptane, cyclooctane, etc., aromatic hydrocarbons such as benzene, toluene, xylene, halogen-substituted aromatic hydrocarbons such as chlorobenzene, bromobenzene, etc., 1,4-dioxane, methyl ethyl ketone, propylene carbonate, trioxaundecane, trimethylolpropane, etc., and the like. Examples of the preferred dispersion medium include oxygen-containing linear hydrocarbons such as rioxanonane, trioxapentadecane, diethylene glycol dimethyl ether, and diethylene glycol diethyl ether; oxygen-containing cyclic hydrocarbons such as tetrahydrofuran; nitrogen-containing saturated hydrocarbons such as triethylamine, propanenitrile, dimethyldiazohexane, trimethyltriazononane, N,N,N',N'-tetramethylethylenediamine, and N,N,N',N",N"-pentamethyldiethylenetriamine; oxygen-containing aromatic hydrocarbons such as anisole; and esters such as butyl butyrate. Preferred dispersion media include those represented by the divalent group R in formula (I).P1 or R P2 When R is a chain alkylene group, examples of the alkylene group include 1,4-dioxane, anisole, diethylene glycol dimethyl ether, and 1,2-dichloroethane. P1 or R P2 When is a cycloalkylene group, examples of the dispersion medium include toluene, anisole, 1,2-dichloroethane, diethylene glycol diethyl ether, N,N,N',N'-tetramethylethylenediamine, and N,N,N',N",N"-pentamethyldiethylenetriamine. Among the above dispersion mediums, it is preferable to use a dispersion medium having excellent solubility for polyalkylene carbonate. Here, "excellent solubility for polyalkylene carbonate" means that 5 g or more of polyalkylene carbonate can be dissolved in 100 g of the dispersion medium.
[0046] (amount of dispersion medium) The amount of the dispersion medium is adjusted so that the solid content of the slurry is at a level that allows coating. Such an amount may vary depending on the type of raw material to be dissolved or dispersed. The solid content of the slurry may be 10% by mass or more, 20% by mass or more, 30% by mass or more, 40% by mass or more, 50% by mass or more, 60% by mass or more, or 70% by mass or more, and is preferably 30% by mass or more. The solid content of the slurry may be 95% by mass or less, 90% by mass or less, 85% by mass or less, 80% by mass or less, 75% by mass or less, 70% by mass or less, 60% by mass or less, or 50% by mass or less, and is preferably 90% by mass or less. In this specification, the solid content of the slurry refers to components other than the dispersion medium (inorganic solid electrolyte, polyalkylene carbonate, stabilizer, active material, etc.).
[0047] [Cathode active material] When the slurry is a positive electrode forming slurry, the slurry contains a positive electrode active material.
[0048] As the positive electrode active material, a known positive electrode active material can be used. Examples of such positive electrode active materials include LiCoO2, LiNiO2, Li 1+x Ni 1 / 3 Mn 1 / 3Co 1 / 3 O2 (x is a positive number), LiMn2O4, Li 1+x Mn 2-x-y M y O4 (M is one or more selected from Al, Mg, Co, Fe, Ni, and Zn; x and y are positive numbers), Li x TiO y (x and y are positive numbers), LiMPO4 (M is Fe, Mn, Co, or Ni), NaCoO2, NaNiO2, Na 1+x Ni 1 / 3 Mn 1 / 3 Co 1 / 3 O2 (x is a positive number), NaMn2O4, Na 1+x Mn 2-x-y M y O4 (M is one or more selected from Al, Mg, Co, Fe, Ni, and Zn; x and y are positive numbers), Na x TiO y (x and y are positive numbers), NaMPO4 (M is Fe, Mn, Co, or Ni), etc.
[0049] (Amount of positive electrode active material) The amount of the positive electrode active material in the slurry solid content may be 10% by mass or more, 30% by mass or more, 50% by mass or more, or 70% by mass or more, and from the viewpoint of realizing a higher energy density, is preferably 80% by mass or more. The amount of the positive electrode active material in the slurry solid content may be 95% by mass or less, 90% by mass or less, 80% by mass or less, or 70% by mass or less.
[0050] [Negative electrode active material] When the slurry is a negative electrode forming slurry, the slurry contains a negative electrode active material.
[0051] As the negative electrode active material, a known negative electrode active material can be used. Examples of such a negative electrode active material include carbon materials such as mesocarbon microbeads, graphite, hard carbon, and soft carbon, Nb2O5, Li4Ti5O 12 , Na4Ti5O 12Examples of the oxide include SiO, metals such as In, Al, Si, Sn, Li, and Na, and alloys of these metals.
[0052] (Amount of negative electrode active material) The amount of the negative electrode active material in the slurry solid content may be 10% by mass or more, 30% by mass or more, or 50% by mass or more, and is preferably 50% by mass or more from the viewpoint of realizing a higher energy density. The amount of the negative electrode active material in the slurry solid content may be 95% by mass or less, 90% by mass or less, 80% by mass or less, or 70% by mass or less.
[0053] [Conductive additive] In the present disclosure, the slurry may contain a conductive assistant when it is a positive electrode forming slurry or a negative electrode forming slurry. Examples of the conductive assistant include carbon black such as acetylene black and ketjen black, carbon nanotubes, natural graphite, artificial graphite, and vapor grown carbon fiber (VGCF). The amount of the conductive assistant varies depending on the type of active material, but is, for example, 0.5 mass% or more in the slurry solid content.
[0054] (Amount of conductive additive) The amount of the conductive assistant varies depending on the electronic conductivity of the active material, but may be 0.1 mass% or more, 0.5 mass% or more, 1 mass% or more, 5 mass% or more, and preferably 0.5 mass% or more, in the slurry solid content. The amount of the conductive assistant may be 25 mass% or less, or 15 mass% or less, and preferably 20 mass% or less, or 10 mass% or less, in the slurry solid content. The above range is suitable from the viewpoint of improving the battery characteristics, and the effects of the present disclosure can be more suitably enjoyed.
[0055] [Other ingredients] The slurry may contain other components within a range that does not impair the effects of the present disclosure. For example, other binder components, other solid electrolytes, other active materials, various inorganic materials such as alkali metal salts, and various additives such as stabilizers can be included. The amount of other components in the slurry is not particularly limited, but may be, for example, 25% by mass or less (for example, 10% by mass or less).
[0056] <Electrolyte layer> The electrolyte layer is obtained by applying an electrolyte layer-forming slurry onto a substrate and drying the applied slurry. The substrate may be a positive electrode or a negative electrode, but may also be another substrate.
[0057] The thickness of the electrolyte layer may be 1 μm or more, 50 μm or more, or 100 μm or more, and may be 600 μm or less, or 300 μm or less. As described in the description of the manufacturing method of the solid-state battery, the thickness of the electrolyte layer may be different before and after the pressing step, and the thickness may be before or after pressing, for example, after pressing.
[0058] The ionic conductivity of the electrolyte layer may be 0.1 mS / cm or more, 0.25 mS / cm or more, 1.0 mS / cm or more, 3.0 mS / cm or more, 10 mS / cm or more, or 30 mS / cm or more. After the pyrolysis step and after pressing, the electrolyte layer may exhibit higher ionic conductivity (e.g., 1.2 times or more, 1.5 times or more, 1.8 times or more, 2.0 times or more, or 2.5 times or more) than before the pyrolysis step due to reduced or absent polyalkylene carbonate and high packing density.
[0059] <Positive electrode> The positive electrode can be obtained by applying a positive electrode-forming slurry onto a substrate and drying the slurry. The substrate may be a positive electrode current collector or an electrolyte layer, but may also be another substrate.
[0060] The positive electrode may be formed on a positive electrode collector. As the positive electrode collector, various materials having excellent electronic conductivity and being difficult to be deteriorated at the charge / discharge potential of the active material used can be used, and examples thereof include aluminum and aluminum alloys. The shape of the positive electrode collector can be, for example, a foil, a plate, a mesh, or the like. The thickness of the positive electrode collector can be determined depending on the dimensions of the electrode body. The thickness of the positive electrode collector may be 1 μm or more, 5 μm or more, 10 μm or more, or 50 μm or more. The thickness of the positive electrode collector may be 500 μm or less, 300 μm or less, or 100 μm or less.
[0061] The thickness of the positive electrode may be 1 μm or more, 10 μm or more, 30 μm or more, or 50 μm or more. The thickness of the positive electrode may be 600 μm or less, 300 μm or less, or 100 μm or less. As described in the description of the manufacturing method of the solid-state battery, the thickness of the positive electrode may be different before and after the pressing step, and the thickness may be before or after pressing, for example, after pressing.
[0062] <Negative electrode> The negative electrode can be obtained by applying the negative electrode-forming slurry onto a substrate and drying the slurry. The substrate may be a negative electrode current collector or an electrolyte layer, but may also be another substrate.
[0063] The negative electrode may be formed on a negative electrode current collector. As the negative electrode current collector, various materials that have excellent electronic conductivity and are not easily altered at the charge / discharge potential of the active material used can be used, and examples thereof include copper, stainless steel, carbon, and carbon-coated copper. The shape of the negative electrode current collector can be, for example, a foil, a plate, a mesh, or the like. The thickness of the negative electrode current collector can be determined depending on the dimensions of the electrode body. The thickness of the negative electrode current collector may be 1 μm or more, 5 μm or more, 10 μm or more, or 50 μm or more. The thickness of the negative electrode current collector may be 500 μm or less, 300 μm or less, 100 μm or less, or 50 μm or less.
[0064] The thickness of the negative electrode may be 1 μm or more, 10 μm or more, 30 μm or more, or 50 μm or more. The thickness of the negative electrode may be 600 μm or less, 300 μm or less, or 100 μm or less. As described in the description of the method for producing a solid-state battery, the thickness of the negative electrode may be different before and after the pressing step, and the thickness may be before or after pressing, for example, after pressing.
[0065] <Solid-state battery manufacturing method> The method for producing a solid-state battery according to the present disclosure may include one or more steps selected from a slurry coating and drying step, a laminate forming step, a thermal decomposition step, and a pressing step. The method for producing a solid-state battery according to the present disclosure may also include a slurry forming step prior to the above steps. It may also include other steps other than those described above.
[0066] [Slurry formation process] The method for producing a solid-state battery according to the present disclosure may include a slurry forming step in which the above-mentioned slurry raw material is dissolved or dispersed in a dispersion medium to form a slurry (slurry for forming an electrolyte layer, a slurry for forming a positive electrode, or a slurry for forming a negative electrode).
[0067] [Slurry application and drying process] In the coating and drying step, the electrolyte layer forming slurry, the positive electrode forming slurry, and the negative electrode forming slurry are each coated on a substrate, and the resulting coating film is then dried to obtain an electrolyte layer, a positive electrode, and a negative electrode, respectively. The substrate to which the slurry is coated may be, for example, a current collector, a solid electrolyte layer, a positive electrode, or a negative electrode. Examples of the coating method include coating with an applicator, a doctor blade, or a bar coater, brush coating, roll coating, spray coating, and electrospray coating. For example, the positive electrode slurry may be coated at regular intervals on a sheet-shaped current collector drawn from a roll.
[0068] [Laminate formation process] The method for manufacturing a solid-state battery according to the present disclosure may include a laminate formation step. In the laminate formation step, a positive electrode and a negative electrode are laminated so as to sandwich the electrolyte layer between the positive electrode and the negative electrode to form a laminate having an electrolyte layer. At this time, the layers may be fixed to each other in the lamination direction by pressing. The obtained laminate has a positive electrode, a negative electrode, and an electrolyte layer located between the positive electrode and the negative electrode. The obtained laminate functions as a solid-state battery, but may be subjected to a pyrolysis step described later.
[0069] [Pyrolysis process] The method for producing a solid-state battery according to the present disclosure may include a decomposition step. In the pyrolysis step, the laminate is heated to pyrolyze the polyalkylene carbonate contained in the electrolyte layer, the positive electrode, or the negative electrode, and remove the polyalkylene carbonate from the laminate. This can improve the battery characteristics.
[0070] The laminate is preferably heated under an inert gas atmosphere such as nitrogen or argon. This can suppress deterioration of the material (e.g., inorganic solid electrolyte) caused by gas or water vapor generated by thermal decomposition of polyalkylene carbonate. The inert gas may be supplied into the heating container as an airflow by being flowed into and discharged from the heating container. The gas or water vapor generated by thermal decomposition of polyalkylene carbonate is ventilated by the inert gas airflow, and deterioration of the material (e.g., inorganic solid electrolyte) can be suppressed well. The heating is preferably performed under reduced pressure. By performing the heating under reduced pressure, there is an advantage that the gas generated by thermal decomposition can be discharged outside the system. When performing the heating under reduced pressure, the vacuum pressure may be 100 Pa or less, 50 Pa or less, or 3 Pa or less. For example, heating under an inert gas airflow and reduced pressure can particularly suppress deterioration of the material.
[0071] The heating temperature may be T-75°C or higher, T-50°C or higher, T°C or higher, or T+10°C or higher, where T°C is the decomposition initiation temperature of the polyalkylene carbonate. The heating temperature may be T+75°C or lower, T+50°C or lower, or T+25°C or lower, preferably T+50°C or lower, where T°C is the decomposition initiation temperature of the polyalkylene carbonate. The heating temperature may be 125°C or higher, 150°C or higher, 175°C or higher, 200°C or higher, 250°C or higher, or 275°C or higher. The heating temperature may be 350°C or lower, 300°C or lower, 200°C or lower, or 175°C or lower. For example, when the polyalkylene carbonate is polyethylene carbonate, it may be in the range of 175°C or more and 275°C or less (e.g., 190°C or more and 230°C or less); when the polyalkylene carbonate is propylene carbonate, it may be in the range of 175°C or more and 275°C or less (e.g., 190°C or more and 230°C or less); and when the polyalkylene carbonate is cyclohexylene carbonate, it may be in the range of 225°C or more and 350°C or less (e.g., 270°C or more and 300°C or less).
[0072] The heating temperature is preferably below a temperature at which the crystal structure of the inorganic solid electrolyte does not change. For example, 75Li2S-25P2S5 (75 and 25 are molar ratios, Li3PS4) is known to be stable at about 300°C or less, and the heating temperature is preferably 300°C or less.
[0073] The heating time may vary depending on the size of the laminate, the number of layers, and the thermal decomposition initiation temperature. The heating time may be 1 minute or more, 3 minutes or more, 5 minutes or more, or 10 minutes or more. The heating time may be 1 hour or less, or 30 minutes or less.
[0074] After the thermal decomposition step, the amount of polyalkylene carbonate remaining in each of the electrolyte layer, the positive electrode, and the negative electrode may be 10% by mass or less, 5% by mass or less, or 1% by mass or less of the amount of polyalkylene carbonate before the thermal decomposition step. The amount of polyalkylene carbonate remaining in the electrolyte layer can be changed by adjusting the heating time in the thermal decomposition step. After the thermal decomposition step, the electrolyte layer may contain a thermal decomposition product of the polyalkylene carbonate. The thermal decomposition product is removed from the system as a gas (e.g., alkylene carbonate), so that usually only a trace amount of the component remains in each member (e.g., 0.1% by mass or less).
[0075] [Pressing process] The method for manufacturing a solid-state battery according to the present disclosure may include a pressing step. In the pressing step, the laminate is pressed in the lamination direction (thickness direction). The pressing step may be performed simultaneously with and / or after the pyrolysis step. This makes the laminate denser, reduces the influence of voids generated by the pyrolysis step, and can provide the effects of improving the strength of the solid-state battery, improving the adhesion of each layer, making the film thickness uniform, and reducing the interface resistance and grain boundary resistance.
[0076] The pressing method may be roll pressing. The roll pressing may be roll-to-roll pressing. The linear pressure of the roll pressing may be 5 kN / cm or more, 50 kN / cm or more, or 100 kN / cm or more, and is preferably 50 kN / cm or more.
[0077] The pressing method may be flat pressing. The surface pressure of the flat pressing may usually be 100 MPa or more.
[0078] After the pressing step, the total thickness of the positive electrode, the electrolyte layer and the negative electrode may be 90% or less, 60% or less, or 40% or less, and is preferably 70% or less, compared to that before the pressing step.
[0079] The pressing step may be carried out under an inert atmosphere such as nitrogen or argon. It is also preferable to carry out the pressing step under reduced pressure. By carrying out the pressing step under reduced pressure, there is an advantage that gas generated by thermal decomposition can be released outside the system.
[0080] [Cutting process] The method for producing a solid-state battery according to the present disclosure may include a cutting step in which the electrode, the electrolyte membrane, or the laminate is cut to a predetermined size.
[0081] [Aggregation process] The manufacturing method of the solid-state battery in the present disclosure may include an assembly step. The solid-state battery may be an assembly of cells in which a positive electrode current collector, a positive electrode, an electrolyte layer, a negative electrode, and a negative electrode current collector are connected in series and / or in parallel to form a cell assembly, with the positive electrode current collector, a positive electrode, an electrolyte layer, a negative electrode, and a negative electrode current collector being regarded as one cell. The assembly step may be carried out, for example, before or after the pyrolysis step, before or after the pressing step, or before or after the cutting step.
[0082] [Enclosure process] The solid-state battery may be installed in a housing while the current collector in the solid-state battery or the extraction electrode electrically connected to the current collector is drawn out to the outside. The drawing position may be opposite to the stacking direction, or may be perpendicular to the stacking direction and in the same direction or opposite direction. Examples of the housing include metal or resin cans, resin film bags, and the like. The shape of the housing is not limited, and may be any of a square type (rectangular parallelepiped type), a cylindrical type, and a laminate pack type. A solid-state battery has an advantage in that it does not require a safety device that is usually provided in a lithium-ion secondary battery.
[0083] <Applications of solid-state batteries> The solid-state battery of the present disclosure can be used as a power source for various applications. Examples of the power source include power sources installed in vehicles (plug-in hybrid vehicles (PHVs), hybrid vehicles (HVs), electric vehicles (EVs), etc.), wearable devices, and various other consumer or industrial devices.
[0084] Although the embodiments have been described above, it will be understood that various changes in form and details are possible without departing from the spirit and scope of the claims.
[0085] For example, the present disclosure also includes the following aspects: [Section 1] A slurry for forming an electrolyte layer, a positive electrode, or a negative electrode in a solid-state battery, the slurry comprises an inorganic solid electrolyte and a polyalkylene carbonate; The slurry, wherein a residual rate of the polyalkylene carbonate after standing in the slurry at a temperature of 25°C for 5 days is 25% or more. [Section 2] the slurry comprises a stabilizer for the polyalkylene carbonate; Item 2. The slurry according to item 1, wherein the stabilizer is at least one selected from the group consisting of a hydroxyl group protecting agent, and a carboxylic acid or a salt thereof. [Section 3] Item 3. The slurry according to item 2, wherein the stabilizer is a dithiophosphine ylide generator. [Section 4] 4. The slurry according to any one of items 1 to 3, wherein the inorganic solid electrolyte is a sulfide solid electrolyte. [Section 5] the slurry comprises a stabilizer for the polyalkylene carbonate and / or a reaction product of the polyalkylene carbonate and the stabilizer; the stabilizer is a dithiophosphine ylide generator, Item 5. The slurry according to any one of items 1 to 4, wherein the inorganic solid electrolyte is a sulfide solid electrolyte. [Section 6] The polyalkylene carbonate has the following formula (I): -(-(C=O)-OR P1 -O-(-R P2 -O-) m -) n - (I) [In the formula, R P1 and R P2 each independently represents a chain alkylene group having 1 to 10 carbon atoms or a cycloalkylene group having 3 to 10 carbon atoms, m is 0, 1 or 2, and n is 10 to 15,000. 6. The slurry according to any one of items 1 to 5, wherein the slurry is represented by the following formula: [Section 7] The amount of the polyalkylene carbonate is 0.1% by mass or more and 40% by mass or less in the slurry solid content, 8. The slurry according to any one of items 2 to 7, wherein the amount of the stabilizer is from 0.1% by mass to 20% by mass based on the polyalkylene carbonate, or from 5 mol % to 1000 mol % based on the polyalkylene carbonate terminal. [Section 8] 8. The slurry according to any one of items 1 to 7, which is for forming an electrolyte layer. [Section 9] 8. The slurry according to any one of items 1 to 7, which is for forming a positive electrode. [Section 10] 8. The slurry according to any one of items 1 to 7, which is for forming a negative electrode. [Section 11] 11. An electrolyte layer, a positive electrode, or a negative electrode obtained by applying and drying the slurry according to any one of items 1 to 10. [Section 12] Item 12. A solid-state battery comprising the electrolyte layer, positive electrode, or negative electrode according to item 11. [Section 13] Item 12. A solid-state battery comprising the electrolyte layer, the positive electrode, or the negative electrode according to item 11, wherein the polyalkylene carbonate is decomposed and removed. [Section 14] The method includes a step of applying and drying the slurry according to any one of items 1 to 10 to obtain an electrolyte layer, a positive electrode, or a negative electrode; How solid-state batteries are manufactured. [Section 15] Item 15. The method for producing a solid-state battery according to item 14, further comprising a pyrolysis step of removing the polyalkylene carbonate in the electrolyte layer, the positive electrode, or the negative electrode by pyrolysis. EXAMPLES
[0086] The present disclosure will be described in detail below with reference to examples, but the present disclosure is not limited to these examples.
[0087] <Abbreviation> The abbreviations used below have the following meanings: LPS: Sulfide solid electrolyte (Li3PS4) PPC: Polypropylene carbonate LR: Lawson's Reagent
[0088] <Example 1 and Comparative Example 1: Thermal Analysis> [Preparation of electrolyte slurry and electrolyte layer] Example 1 An anisole solution containing 20% by mass of PPC (Mw360000) was prepared, Lawson's reagent (LR) was added so that PPC:LR = 100:3 (weight ratio), and the mixture was stirred at 120 ° C for 5 minutes to dissolve. 1.0 g of anisole was added to 0.3 g of this (PPC + LR) anisole solution and dissolved. 1 g of sulfide-based solid electrolyte (LPS) was further added and mixed with a planetary stirring and degassing device (Kurabo Mazerustar KK-250S) to prepare a solid electrolyte layer forming slurry with a solid content concentration of 46% and a composition ratio of LPS: (PPC + LR) = 100: 6 (weight ratio). The obtained solid electrolyte layer forming slurry was applied and then dried at room temperature for 24 hours to obtain an electrolyte layer. Separate from the electrolyte layer, the solid electrolyte slurry was vacuum dried at 40 ° C for 1 hour to obtain a (PPC + LR)-containing electrolyte powder.
[0089] Comparative Example 1 An electrolyte slurry, an electrolyte powder, and an electrolyte layer were obtained in the same manner as in Example 1, except that Lawesson's reagent was not used and the weight ratio was LPS:PPC=100:6.
[0090] [TG / DTA measurement] Using the obtained electrolyte powder, a TG / DTA (PerkinElmer Japan, Thermogravimetric / Calorimetric Simultaneous Measurement Device STA6000) was installed in a glove box with a dew point of -100°C and an argon atmosphere, and the measurement was performed under the following conditions: the temperature was raised from 30°C to 200°C at a rate of 10°C / min, and then the temperature was maintained at 200°C for 60 minutes. The results are shown in Figure 1.
[0091] From the results in FIG. 1, it was found that in the presence of an inorganic solid electrolyte, the decomposition onset temperature of the polyalkylene carbonate was about 80° C. in Comparative Example 1 in which Lawson's reagent was not used, whereas the decomposition onset temperature was about 122° C. in Example 1 in which Lawson's reagent was coexisted, and the presence of Lawson's reagent improved the thermal stability of the polyalkylene carbonate in the electrolyte.
[0092] [Stability of electrolyte layer over time] When the obtained electrolyte layer was observed after 2 weeks, cracks and peeling from the substrate were observed in the electrolyte layer of Comparative Example 1. On the other hand, no cracks or peeling from the substrate were observed in the electrolyte layer of Example 1. This was not limited to the electrolyte layer, but was also observed in the experiments with the positive and negative electrodes.
[0093] <Examples 2 to 6 and Comparative Examples 2 to 3: Measurement of decomposition rate by IR> [Preparation of electrolyte slurry] An anisole solution containing 20% by mass of PPC was prepared, Lawson's reagent (LR) was added so that PPC:LR = 100:Y (weight ratio), and the mixture was stirred at 120 ° C for 5 minutes to dissolve. 1.0 g of anisole was added to 0.3 g of this (PPC + LR) anisole solution and dissolved. 1 g of sulfide-based solid electrolyte (LPS) was further added and mixed with a planetary stirring and degassing device (Kurabo Mazerustar KK-250S) to prepare a solid electrolyte slurry with a solid content concentration of 46% by mass and a composition of LPS: (PPC + LR) = 100:X (weight ratio). The obtained inorganic solid electrolyte slurry was left to stand for N days at a temperature of 25 ° C and a dew point temperature of -85 ° C.
[0094] [Molecular weight measurement] The molecular weight of PPC was measured using a Waters 2695 separation module manufactured by Nihon Waters and equipped with a column (Shodex OHPac SB-800 series, a product name of Showa Denko K.K.) at a column temperature of 40°C, a 0.03 mol / L lithium bromide-N,N-dimethylformamide solution as the eluent, and a flow rate of 0.65 mL / min, and then compared with that of polystyrene having a known mass average molecular weight measured under the same conditions.
[0095] [Remaining rate calculation formula] The residual rate of PPC after standing was measured by IR at 1749 cm -1 The peak intensity of 1809 cm belongs to the decomposition product propylene carbonate. -1 The peak intensity was calculated from the following formula. Survival rate (%)=1749cm -1 Peak intensity / (1809cm -1 Peak intensity of +1749cm -1 (peak intensity)*100 The IR was measured by the following method. Anisole (10 ml) was added to the obtained inorganic solid electrolyte slurry after standing for N days, and the mixture was centrifuged (5000 rpm for 1 h), and the supernatant was separated. IR measurement (ATR method) was performed using an FT-IR device (JASCO Corporation, FT / IR-4100) equipped with a single reflection ATR with a diamond prism, with a measurement range of 7800 cm -1 ~350cm -1 , 64 integrations, resolution 4cm -1 The experiment was carried out by dropping 0.5 ml of the sample onto a prism under the conditions of 0.1% transmittance (T%). Anisole was measured as the blank, and the supernatant was measured as the sample. The difference between the results of the graphs was taken as the extracted components.
[0096] The results are summarized in the table below. [Table 1: Changes in LR addition amount (using PPC for control 1)] TIFF2025039023000006.tif49108
[0097] [Table 2: No LR, change in standing time (using PPC of control 1)] TIFF2025039023000007.tif2785
[0098] [Table 3: LPS content reduced product (using PPC of control 2)] TIFF2025039023000008.tif3486
[0099] It was found that the presence of Lawesson's reagent improves the stability of polyalkylene carbonate in the slurry. Since the effect is remarkable when Lawesson's reagent is added in a stoichiometric ratio or more to the PPC terminal, it is presumed that Lawesson's reagent acts on the PPC terminal to suppress decomposition.
Claims
1. A slurry for forming an electrolyte layer, a positive electrode, or a negative electrode in a solid-state battery, The slurry comprises an inorganic solid electrolyte, a polyalkylene carbonate, and a stabilizer for the polyalkylene carbonate.
2. The slurry according to claim 1 , wherein the stabilizer is at least one selected from the group consisting of a hydroxyl group protecting agent, and a carboxylic acid or a salt thereof.
3. 3. The slurry of claim 2, wherein the stabilizing agent is a dithiophosphine ylide generator.
4. 2. The slurry of claim 1, wherein the inorganic solid electrolyte is a sulfide solid electrolyte.
5. the slurry comprises a stabilizer for the polyalkylene carbonate and / or a reaction product of the polyalkylene carbonate and the stabilizer; the stabilizer is a dithiophosphine ylide generator, 2. The slurry of claim 1, wherein the inorganic solid electrolyte is a sulfide solid electrolyte.
6. The polyalkylene carbonate has the following formula (I): -(-(C=O)-O-R P1 -O-(-R P2 -O-) m -) n - (I) [In the formula, R P1 and R P2 each independently represents a chain alkylene group having 1 to 10 carbon atoms or a cycloalkylene group having 3 to 10 carbon atoms, m is 0, 1 or 2, and n is 10 to 15,000. The slurry of claim 1 , wherein
7. The slurry according to claim 1 , which is for forming an electrolyte layer.
8. The slurry according to claim 1 , which is for forming a positive electrode.
9. The slurry according to claim 1 , which is for forming a negative electrode.
10. An electrolyte layer, a positive electrode, or a negative electrode obtained by applying and drying the slurry according to any one of claims 1 to 9.
11. A solid-state battery comprising the electrolyte layer, the positive electrode, or the negative electrode according to claim 10, wherein the polyalkylene carbonate has been decomposed and removed.
12. The method includes a step of applying and drying the slurry according to any one of claims 1 to 9 to obtain an electrolyte layer, a positive electrode, or a negative electrode. How solid-state batteries are manufactured.
Citation Information
Patent Citations
All solid state secondary-battery additive, all-solid-state secondary battery, and method for producing same
WO2017030127A1